2011
DOI: 10.1111/j.1835-2561.2011.00140.x
|View full text |Cite
|
Sign up to set email alerts
|

The Communicative Value of the Auditor's Report

Abstract: Communicating the results of the audit is a crucial part of the audit process. This potentially enables the users of financial reports to assess the quality of the audit, which will in turn contribute to their assessments of financial reporting quality. This research reports the results of a verbal protocol study of 16 financial analysts to assess how they use an auditor's report as part of a company evaluation. Auditors’ reports perse are found to be important to analysts in that they signal a level of reliab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 20 publications
(24 reference statements)
1
37
0
5
Order By: Relevance
“…One of the purposes of the new audit report is to reduce the expectation and information gaps between users and auditors by improving the auditors’ communication by adding more information to the report (Church et al., ). The International Auditing and Assurance Standards Board (IAASB) () defines the expectation gap as the “difference between what users expect from the auditor and the financial statement audit and the reality of what an audit is.” It goes on to define the information gap as the “gap between the information users believe is needed to make informed investment and fiduciary decisions, and what is available to them through the entity's audited financial statements or other publicly available information.” Previous studies show mixed results for the changes to the audit report and the reduction in the expectation gap (Church et al., ; Coram, Mock, Turner, & Gray, ; Geiger, ; Gray, Turner, Coram, & Mock, ; Miller, Reed, & Strawser, ; Mock et al., ; Turner, Mock, Gray, & Coram, ) but provide evidence that the information gap may be reduced when information in the audit report increases (CFA Institute ; IAASB ; IOSCO ).…”
Section: Literature Review and Hypothesesmentioning
confidence: 95%
“…One of the purposes of the new audit report is to reduce the expectation and information gaps between users and auditors by improving the auditors’ communication by adding more information to the report (Church et al., ). The International Auditing and Assurance Standards Board (IAASB) () defines the expectation gap as the “difference between what users expect from the auditor and the financial statement audit and the reality of what an audit is.” It goes on to define the information gap as the “gap between the information users believe is needed to make informed investment and fiduciary decisions, and what is available to them through the entity's audited financial statements or other publicly available information.” Previous studies show mixed results for the changes to the audit report and the reduction in the expectation gap (Church et al., ; Coram, Mock, Turner, & Gray, ; Geiger, ; Gray, Turner, Coram, & Mock, ; Miller, Reed, & Strawser, ; Mock et al., ; Turner, Mock, Gray, & Coram, ) but provide evidence that the information gap may be reduced when information in the audit report increases (CFA Institute ; IAASB ; IOSCO ).…”
Section: Literature Review and Hypothesesmentioning
confidence: 95%
“…As a result, numerous recent studies have suggested a range of disclosures in the audit report to fill the information gap (see, for example, CFA Institute ; Coram et al. ; Gray et al. ).…”
Section: Implications Of the Audit Reformsmentioning
confidence: 99%
“…This issue is even more contentious given that there is evidence that users do not read the entire audit report (Coram et al. ).…”
Section: Implications Of the Audit Reformsmentioning
confidence: 99%
See 1 more Smart Citation
“…Turner et al (2010), citing Mock et al (2009), provide evidence that non-professional investors do not use audit reports at all, and that analysts pay attention to the existence, but not the form, of audit reports. Coram et al (2011) extended these studies, noting that the ''standard nature'' of the unqualified audit report causes analysts to not consider audit report content in corporate valuation analyses. These findings imply that financial statement users need information beyond the standard audit report to assist with investment decisions.…”
Section: Prior Academic Researchmentioning
confidence: 99%